At genplacere den moderne stat - Guvernementalitet og de politiske idéers historie - Saar, Martin (Slagmark - Tidsskrift for idéhistorie, 2018)
Michel Foucault never wrote very comprehensively about his method in regards to his approach to the history of political ideas and the emergence of the modern state, something he most explicitly tried to do in the two lectures which he himself termed ’a history of governmentality’, Security, Territory, Population (1977-78) and The Birth of Biopolitics (1978-79). This article treats these reflections as a ’methodological promise’ and seeks to reconstruct a Foucauldian approach to the history of political ideas from the role Foucault himself believed the ’history of governmentality’ should play. Foucault’s approach proves to be a distinct way of studying the history of political ideas as an alternative to, and in some ways superior to, both the more traditional ways of doing the history of political ideas as well as newer attempts such as intellectual history and conceptual history. In the special way it looks at the history of political thought, Foucault’s approach can go much further than the other alternatives.